Comparison of osteogenic differentiation potential of induced pluripotent stem cells on 2D and 3D polyvinylidene fluoride scaffolds. Issue 10 (9th March 2019) - Mirzaei, Ali; Moghadam, Abbas Shapouri; Abazari, Mohamad Foad; Nejati, Fatemeh; Torabinejad, Sepehr; Kaabi, Mohamad; Enderami, Seyed Ehsan; Ardeshirylajimi, Abdolreza; Darvish, Maryam; Soleimanifar, Fatemeh; Saburi, Ehsan
Abstract: In recent decades, tissue engineering has been the most contributor for introducing 2D and 3D biocompatible osteoinductive scaffolds as bone implants. Polyvinylidene fluoride (PVDF), due to the unique mechanical strength and piezoelectric properties, can be a good choice for making a bone bioimplant. In the present study, PVDF nanofibers and film were fabricated as 3D and 2D scaffolds, and then, osteogenic differentiation potential of the human induced pluripotent stem cells (iPSCs) was investigated when grown on the scaffolds by evaluating the common osteogenic markers in comparison with tissue culture plate. Biocompatibility of the fabricated scaffolds was confirmed qualitatively and quantitatively by the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide and scanning electron microscopy assays. Human iPSCs cultured on PVDF nanofibers showed a significantly higher alkaline phosphate activity and calcium content compared with the iPSCs cultured on PVDF film. Osteogenic‐related genes and proteins were also expressed in the iPSCs seeded on PVDF nanofibers significantly higher than iPSCs seeded on PVDF film, when investigated by real‐time reverse transcription polymerase chain reaction and western blot analysis, respectively. According to the results, the PVDF nanofibrous scaffold showed a greater osteoinductive property compared with the PVDF film and due to the material similarity of the scaffolds, it could be concluded that the 3D structure could lead to better bone differentiation. Taken together, the obtained results demonstrated that human iPSC‐seeded PVDF nanofibrous scaffold could be considered as a promising candidate for use in bone tissue engineering applications. Abstract : Polyvinylidene fluoride (PVDF), due to the unique mechanical strength and piezoelectric properties, can be a good choice for making a bone bioimplant. PVDF nanofibers and film were fabricated as 3D and 2D scaffolds and their osteoinductive potential investigated by culturing of the human induced pluripotent stem cells (iPSCs) and evaluation of the common osteogenic markers. Biocompatibility of the scaffolds was confirmed by the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) and scanning electron microscopy (SEM) assays that were not significantly different. Their osteoinductivity was also confirmed by alkaline phosphate (ALP) activity, calcium content, and gene and protein expression, while the PVDF nanofibrous scaffold showed a greater osteoinductive property than the PVDF film and due to the similarity of polymer type in two scaffolds, it could be concluded that a 3D structure could lead to better bone differentiation.